Most chilblains observed during the COVID‐19 outbreak occur in patients who are negative for COVID‐19 on polymerase chain reaction and serology testing. (1st November 2020) - Le Cleach, L.; Dousset, L.; Assier, H.; Fourati, S.; Barbarot, S.; Boulard, C.; Bourseau Quetier, C.; Cambon, L.; Cazanave, C; Colin, A.; Kostrzewa, E.; Lesort, C.; et al.
Summary: Background: Acral lesions, mainly chilblains, are the most frequently reported cutaneous lesions associated with COVID‐19. In more than 80% of patients tested, nasopharyngeal swabs were negative on reverse transcription polymerase chain reaction (RT‐PCR) for SARS‐CoV‐2 when performed, and serology was generally not performed. Methods: A national survey was launched on 30 March 2020 by the French Society of Dermatology asking physicians to report cases of skin manifestations in patients with suspected or confirmed COVID‐19 by using a standardized questionnaire. We report the results for acral manifestations. Results: We collected 311 cases of acral manifestations [58.5% women, median age 25.7 years (range 18–39)]. The most frequent clinical presentation (65%) was typical chilblains. In total, 93 cases (30%) showed clinical suspicion of COVID‐19, 67 (22%) had only less specific infectious symptoms and 151 (49%) had no clinical signs preceding or during the course of acral lesions. Histology of skin biopsies was consistent with chilblains. Overall, 12 patients showed significant immunological abnormalities. Of the 150 (48%) patients who were tested, 10 patients were positive. Seven of 121 (6%) RT‐PCR‐tested patients were positive for SARS‐CoV‐2, and five of 75 (7%) serology‐tested patients had IgG anti‐SARS‐CoV‐2. Tested/untested patients or those with/without confirmed COVID‐19 did not differ in age, sex, history or acral lesion clinical characteristics. Conclusions: The results of this survey do not rule out that SARS‐CoV‐2 could be directly responsible for some cases of chilblains, but we found no evidence of SARS‐CoV‐2 infection in the large majority of patients with acral lesions during the COVID‐19 lockdown period in France. What is already known about this topic? About 1000 cases of acral lesions, mainly chilblains, were reported during the COVID‐19 outbreak. Chilblains were reported to occur in young people within 2 weeks of infectious signs, which were mild when present. Most cases did not have COVID‐19 confirmed by reverse transcription polymerase chain reaction (RT‐PCR), and few serology results were available. What does this study add? Among 311 patients with acral lesions, mainly chilblains, during the COVID‐19 lockdown period in France, the majority of patients tested had no evidence of SARS‐CoV‐2 infection. Overall, 70 of 75 patients were seronegative for SARS‐Cov‐2 serology and 114 of 121 patients were negative for SARS‐CoV‐2 RT‐PCR.